CONWIP implementation in a system with cross-trained teams. Issue 20 (18th October 2019) - Olaitan, Oladipupo; Alfnes, Erlend; Vatn, Jørn; Strandhagen, Jan Ola
Abstract : Although a significant amount of research exists on the implementation of the CONstant Work In Process (CONWIP) production control strategy in different types of manufacturing environments, the challenge posed by the complex flow of multiple products through the case manufacturing system of this work necessitates defining a unique type of item release rule to operate with the CONWIP control. The case system is a chair cover production line, which has sets of cross-trained teams that can process its different product models with different levels of efficiency. This work focusses on the CONWIP control strategy, but with the introduction of a new item release rule for prioritising items for release into the system. Results from simulation experiments show that operating CONWIP with an item release rule that is synchronised with the work rate of each of the system's cross-trained teams improves its performance. In comparison with a First in First out (FIFO) rule, this item release rule shortens the system throughput time. It also increases the chances of items being processed by the team most suitable for them, thereby minimising the quality and efficiency issues that might occur in systems that consist of teams with varying levels of proficiency for processing the different product models. Irrespective of the item release rule that is applied, CONWIP achieves a better distribution of workload amongst the teams than a Push control achieves.